Aspirational and representative constitutional identity in Africa. Issue 1 (12th March 2023) - Erk, Jan
Abstract: This article addresses the problématique of giving voice to homegrown traditions of constitutionalism in individual African countries. The scholarly discussion is combined with an applied concern about whether this could instil a wider grassroots embrace of the country's constitution, thereby consolidating constitutionalism and ensuring longevity. The investigation is carried through the lens of two sub-categories of the concept of constitutional identity: a representative one that reflects a country's particular political, social and cultural makeup, and an aspirational one that sets goals and ideals. The challenge, in both scholarly and applied terms, is how to ensure that a constitution instils a sense of public ownership by becoming more representative of a country's underlying makeup while also giving voice to modern aspirations to protect and promote individual human rights, and in doing so, also becoming self-sustaining as the foundational basic law guiding future generations. Attention is paid not only to the forms of constitutions but also to their function in both reaching ideals (in the positive sense of success) and staving off pitfalls (in the negative sense of success). The article also discusses whether these are best achieved through gradual terms over time or through the sudden big bang of mega reforms.